FERMENTATION OF BITTER MUSTARD GREENS (Brassica juncea (L.) Czern.: PHYTOCHEMICAL SCREENING, PROXIMATE COMPOSITION, AND ISOLATION OF LACTIC ACID BACTERIA - Nasri, Nasri; Cintya, Henni; Haro, Ginda; Silalahi, Jansen; Pakpahan, Gita Asima E.; Sitanggang, Sarah Novia S.; Sefira, Inka (Talenta Publisher, 2025)
Fermented vegetables are widely consumed functional foods, but scientific data on traditionally fermented bitter mustard greens are still limited. This study aimed to evaluate the phytochemical profile and proximate composition of Brassica juncea after spontaneous fermentation and to isolate lactic acid bacteria (LAB) formed during the process. A laboratory experimental design was applied; bitter mustard greens were spontaneously fermented in brine for seven days at room temperature. Daily changes in pH and organoleptic characteristics were recorded. Phytochemical screening was performed on fresh and fermented samples (leaves, stems, brine). Proximate analysis included moisture, ash, acid-insoluble ash, crude fat, protein, and carbohydrates using AOAC methods. LAB were isolated on MRS–CaCO₃ agar and characterized phenotypically. Fermentation produced a progressive decrease in pH (from 5.0 to 2.9–3.3) accompanied by sour aroma and yellowish discoloration, indicating active lactic acid fermentation. Flavonoids, phenolics, and terpenoids were present in both fresh and fermented samples, although weaker reactions occurred in stems and brine. Proximate analysis revealed very high moisture content (88.76–95.20%), low protein (0.53–0.88%), low fat (5.03–5.50%), and low residual carbohydrates. LAB isolates (ASP-CF, ASP-B, ASP-D) were Gram-positive, catalase-negative, acid-producing, and non-H₂S-forming. In conclusion, traditional spontaneous fermentation of Brassica juncea produces a LAB-dominated fermented product that retains major phytochemical groups and exhibits proximate characteristics typical of fermented vegetables, supporting its potential as a functional food. Further molecular identification of LAB and quantitative metabolite profiling are recommended.